Assessment and intervention with mothers and partners following child sexual abuse: empowering to protect - Still, Jenny (Jessica Kingsley Publishers, 2016)
Introduction -- The complexity of assessing non-offending mothers and partners -- Did she know? can she protect? : belief, disbelief and denial -- The addition of the offender perspective to our understanding of mothers and partners -- Understanding sex offenders : how much do we need to know and why? -- Two simple models for understanding sex offenders for use when working with mothers and partners -- Applying knowledge of sex offenders when working with mothers and partners -- The impact of the offender on the mother/child relationship -- The effect of the offender on family dynamics -- What can hinder a good assessment? : the need to see it from the mother's or partner's perspective -- Are we all speaking the same language? : the need for improved inter-agency understanding -- Assessment of the mother/partner : pre-assessment planning -- The importance of engagement and motivation -- The assessment interview: what questions to ask, why, how and when -- Intervention : empowering mothers and partners to assist and to protect their child and family